The Effect of Motivation and Work Discipline on Teacher Achievement - Sapto Rahardjo; Djoko Soelistya; Mahjudin (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This research was conducted to find out things that affect Teacher Achievement at the Muhammadiyah Driyorejo Gresik Charity. The study aims to analyze whether Motivation has a direct effect on Teacher Achievement, Work Discipline has a direct effect on Teacher Achievement, Motivation has a direct effect on Organizational Commitment, Work Discipline has a direct effect on Organizational Commitment, Motivation has an indirect effect on Teacher Achievement with Organizational Commitment as a mediating variable, and Work Discipline has an indirect effect on Teacher Achievement with Organizational Commitment as a mediating variable. The research method used in this research is quantitative. The population in this study were all teachers at the Muhammadiyah Driyorejo Gresik Charity, with saturated sampling totaling 110 respondents. Data analysis using Smart-PLS. The results showed that Motivation has a positive and significant influence on Teacher Achievement. Discipline has a positive and significant influence on Teacher Achievement. Motivation has a positive and significant influence on Organizational Commitment. Discipline has a positive and significant influence on Organizational Commitment. Organizational Commitment has a positive and significant influence on Teacher Achievement. Motivation has a positive and significant influence on Teacher Achievement through Organizational Commitment. Based on the value of H1 of 2.838, greater than H6 of 2.040, this indicates a partial mediation effect. Discipline has a positive and significant influence on Teacher Performance through Organizational Commitment. Based on the value of H2 of 2,250, smaller than H7 of 2,504, this indicates a partial mediating effect.